Ultra high stable supercapacitance performance of conducting polymer coated MnO2 nanorods/rGO nanocomposites. Issue 32 (5th April 2017) - Hareesh, K.; Shateesh, B.; Joshi, R. P.; Williams, J. F.; Phase, D. M.; Haram, S. K.; Dhole, S. D.
Abstract : Schematic representation of the preparation of a MGP nanocomposite and its ultra-high stable supercapacitance. Abstract : A ternary nanocomposite that consists of MnO2 nanorods and reduced graphene oxide sheets supported on poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) polymer has been developed for supercapacitor applications. X-ray diffraction, field emission scanning electron microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, the Brunauer–Emmett–Teller method and X-ray photoelectron spectroscopic analysis confirmed the formation of a ternary nanocomposite of PEDOT:PSS/MnO2 nanorods/rGO. Electrochemical investigation of these materials in acetonitrile containing lithium per chlorate demonstrated an enhanced specific capacitance of 633 F g −1 at a current density of 0.5 A g −1 and 100% stability up to 5000 charging–discharging cycles at 1 A g −1 . The enhanced capacitance and working stability of the PEDOT:PSS/MnO2 nanorods/rGO nanocomposite along with the simplicity in making the active materials make this system a promising candidate for the commercial development of supercapacitors.